The Effect of Training on Teachers' Ability to Develop Quiziz Media to Train Students' Communication Skills - Fini Alfionita Umar; Sri Wahyuni; Andreas Suparman; Rosi Vera; Ida Kaniawati; Achmad Samsudin (Universitas Lambung Mangkurat, 2024)
Communication skills are 21st-century skills that students must grow and develop. One learning innovation that is suitable for teachers to use to improve student's communication skills is the use of interactive learning media. Therefore, this research aims to measure teachers' skills in developing interactive media using the Quizizz platform to improve students' communication skills. This research uses a quantitative descriptive method with a pre-experimental research design. Activities are carried out through webinars, guidance and training over four weeks. A total of 21 teachers were selected as the mitre to have their skills measured, and it was found that their skills in using digital technology with web-based interactive media via the Quizizz platform had increased. The results of community service show that 61.9% of partners feel that their ability to design interactive learning media is very developed, and 38.1% feel that their ability to design interactive learning media is quite developed. Meanwhile, regarding the ability to design communication-oriented physics learning, 90.4% of partners felt very developed and 9.5% felt developed. This shows the success of implementing community service.